Disseminated Mycobacterium abscessus Infection Following Septic Arthritis. Issue 21 (May 2015) - Fukui, Shoichi; Sekiya, Noritaka; Takizawa, Yasunobu; Morioka, Hiroshi; Kato, Hirofumi; Aono, Akio; Chikamatsu, Kinuyo; Mitarai, Satoshi; Kobayashi, Satomi; Kamei, Satoshi; Setoguchi, Keigo; Yong., Tuck Yean
<x xml:space="preserve">Abstract</x> Abstract Mycobacterium abscessus is a rapidly growing mycobacterium found mainly in patients with respiratory or cutaneous infections, but it rarely causes disseminated infections. Little is known about the clinical characteristics, treatment, and prognosis of disseminated M abscessus infection. A 75-year-old Japanese woman who had been treated for 17 years with a corticosteroid for antisynthetase syndrome with antithreonyl-tRNA synthetase antibody developed swelling of her right elbow. X-ray of her right elbow joint showed osteolysis, and magnetic resonance imaging revealed fluid in her right elbow joint. M abscessus grew in joint fluid and blood cultures. She was diagnosed with a disseminated M abscessus infection following septic arthritis. Antimicrobial treatment by clarithromycin, amikacin, and imipenem/cilastatin combined with surgical debridement was administered. Although blood and joint fluid cultures became negative 1 week later, the patient died at 6 weeks from starting antimicrobial treatment. We reviewed 34 cases of disseminated M abscessus infections from the literature. Most of the patients had immunosuppressive backgrounds such as transplantation, use of immunosuppressive agents, hematological malignancy, and end stage renal disease. The duration from onset of symptoms to diagnosis was over 3 months in half of the cases. All fatal cases had positive blood cultures or use of immunosuppressive agents. Clinicians should bear in mind that mycobacterial infections including M abscessus are one of the differential diagnoses in patients with subacute arthritis and soft tissue infections.